Women in historical and archaeological video games - Draycott, Jane (Video games and the humanities, 2022)
This volume focuses on the depiction of women in video games set in historical periods or archaeological contexts, explores the tension between historical and archaeological accuracy and authenticity, examines portrayals of women in historical periods or archaeological contexts, portrayals of female historians and archaeologists, and portrayals of women in fantastical historical and archaeological contexts. It includes both triple A and independent video games, incorporating genres such as turn-based strategy, action-adventure, survival horror, and a variety of different types of role-playing games. Its chronological and geographical scope ranges from late third century BCE China, to mid first century BCE Egypt, to Pictish and Viking Europe, to Medieval Germany, to twentieth century Taiwan, and into the contemporary world, but it also ventures beyond our universe and into the fantasy realm of Hyrule and the science fiction solar system of the Nebula
Keywords: Aufsatzsammlung; Feminismus; Authentizität; Geschlechterrolle; Frau; Archäologie; Geschichtsdarstellung; Computerspiel